Coexistence of banks and non-banks: Intermediation functions and strategies - Nicola Cetorelli; Gonzalo Cisternas; Asani Sarkar (Federal Reserve Bank of New York, 2025)
What is the essence of non-bank financial intermediation? How does it emerge and interact with intermediation performed by banks? To investigate these questions, we develop a model-based survey: we classify existing models into different intermediation functions á la Merton (1995) to show that variations of them admit a common modeling structure; then, we extend or reinterpret the resulting models to connect equilibrium strategies to non-bank activities in practice. Particular emphasis is placed on the coexistence of banks and non-banks: how their competition, or the extent of cooperation through contractual arrangements, varies across intermediation functions. Through this approach we speak to a variety of entities such as traditional banks, open-end funds, special purpose vehicles, private credit entities, and fintech lenders. We also discuss innovation, regulation, and market liquidity as drivers of non-bank activities.
Keywords: G21; G23; G18; 330; non-banks; banks; financial intermediation